Eya‐six are necessary for survival of nephrogenic cord progenitors and inducing nephric duct development before ureteric bud formation - Xu, Jinshu; Xu, Pin‐Xian (Developmental dynamics, 2015)
Background: Specification of the metanephric mesenchyme is a central step of kidney development as this mesenchyme promotes nephric duct induction to form a ureteric bud near its caudal end. Before ureteric bud formation, the caudal nephric duct swells to form a pseudostratified epithelial domain that later emerges as the tip of the bud. However, the signals that promote the formation of the transient epithelial domain remain unclear. Here, we investigated the early roles of the mesenchymal factor Six family and its cofactor Eya on the initial induction of nephric duct development. Results: The nephrogenic progenitor population is initially present but significantly reduced in mice lacking both Six1 and Six4 and undertakes an abnormal cell death pathway to be completely eliminated by ∼E10.5–E11.0, similar to that observed in Eya1‐/‐ embryos. Consequently, the nephric duct fails to be induced to undergo normal proliferation to pseudostratify and form the ureteric bud in Six1‐/‐;Six4‐/‐ or Eya1‐/‐ embryos. Conclusions: Our data support a model where Eya‐Six may form a complex to regulate nephron progenitor cell development before metanephric specification and are critical mesenchymal factors for inducing nephric duct development. Developmental Dynamics 244:866–873, 2015. © 2015 Wiley Periodicals, Inc. Key Findings Nephrogenic progenitor population is reduced in Six1 single mutant and markedly reduced in Six1;Six4 double mutant embryos at E9.5 Initial induction of the nephric duct for ureteric development is blocked in mice lacking Six1/Six4 or Eya1 Nephrogenic cord progenitors undergo abnormal cell death in mice lacking Six1;Six4 or Eya1